Responses to Tsunami and War Trauma Through the Musical Arts in Aceh, 2005–2012 - Margaret Kartomi (Wacana Seni Journal of Arts Discourse, 2014)
This article traces the musical responses to the Acehnese people's trauma, i.e., the emotional wounds caused by their stressful and life-threatening experiences resulting from (1) the conflict between the Aceh independence movement and the Indonesian army in 1976-2005 and (2) the tsunami that hit its western and northern shores in 2004. Some devastated performing groups were reformed, or new ones created, by key people who initiated them and taught children to perform the traditional dances and music. After the conflict ceased in 2005 joyous villagers started performing again at weddings and other life event celebrations that they had postponed due to the frequent curfews. Convinced of the healing properties of the arts, performing groups performed war and tsunami-related songs and composers wrote songs to poetry that expressed the victim's trauma. In the years following the tsunami the national and local media broadcast emotional songs expressive of the people's losses and grief, and government organised commemorations and festivals to encourage the victims and others from all over the province to perform therapeutic music and dance. This Acehnese study suggests that when a people experience not just one but two disasters that the effects of the second can partly displace the first and bring about gradual resolution of both trauma, but only if determined, prolonged efforts are made to resolve them over time.